2021
DOI: 10.21873/invivo.12534
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Oral Recombinant Methioninase and Eribulin on a PDOX Model of Triple-negative Breast Cancer (TNBC) Liver Metastasis

Abstract: Background/Aim: The aim of the present study was to identify effective drugs for a highly-aggressive livermetastasis of triple-negative breast cancer (TNBC) in a patientderived orthotopic xenograft (PDOX) mouse model. Drugs tested were oral recombinant methioninase (o-rMETase), lowdose eribulin and their combination. Materials and Methods: Patient-derived TNBC was implanted in the liver of nude mice by surgical hepatic implantation. Two weeks after transplantation, 32 mice were randomized (n=8 per group) into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…PDX models reproduce the clinicopathological characteristics of the original tumor and are used as experimental models for drug evaluation, biomarker identification, and precision medicine strategies [ 6 ]. Several PDX models have been established successfully, including colon [ 9 ], stomach [ 10 ], breast [ 11 ], pancreas [ 12 ], lung [ 13 ], liver [ 14 ], kidney [ 15 ], bladder [ 16 ], uterus [ 17 ], and ovary [ 18 ]. However, a limited number of studies have reported PDX models of cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…PDX models reproduce the clinicopathological characteristics of the original tumor and are used as experimental models for drug evaluation, biomarker identification, and precision medicine strategies [ 6 ]. Several PDX models have been established successfully, including colon [ 9 ], stomach [ 10 ], breast [ 11 ], pancreas [ 12 ], lung [ 13 ], liver [ 14 ], kidney [ 15 ], bladder [ 16 ], uterus [ 17 ], and ovary [ 18 ]. However, a limited number of studies have reported PDX models of cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Although we have previously reported the efficacy of oral rMETase in many types of cancer in vivo (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(61)(62), this is the first report that shows oral administration of E. coli JM109-rMETase inhibits tumor growth. When E. coli is administered orally, its toxicity to mice should be considered.…”
Section: Discussionmentioning
confidence: 82%
“…rMETase was initially administered by intravenous or intraperitoneal injection. However, recently we showed that rMETase was highly effective when administered orally (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54). However, oral administration of methioninase requires multiple doses each day.…”
mentioning
confidence: 99%
“…We originally discovered that methionine restriction is highly synergistic with chemotherapy in 1986 (28). Since that original publication, many studies have shown synergy of methionine restriction with chemotherapy (32,33), including methionine restriction with rMETase (15,(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44). The combination of methionine restriction and chemotherapy is termed the Hoffman protocol (45).…”
Section: Discussionmentioning
confidence: 99%
“…We have produced recombinant methioninase (rMETase) (12), an enzyme that catabolizes methionine, and have demonstrated the effectiveness of rMETase in breast cancer using patientderived orthotopic xenograft (PDOX) models (13)(14)(15)(16).…”
mentioning
confidence: 99%